2011
DOI: 10.1007/s10551-011-0818-9
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Salience Revisited: Refining, Redefining, and Refueling an Underdeveloped Conceptual Tool

Abstract: legitimacy, stakeholder identification, stakeholder salience, power, urgency,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
261
2
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(286 citation statements)
references
References 94 publications
(202 reference statements)
12
261
2
11
Order By: Relevance
“…This attitude enables the maximization and maintenance of a favorable position in relation to all organizational interests in strategic decision making (Friedman et al, 2004). Thus, successful organizational management depends on the correct identification of stakeholders and subsequent assessment of their actual relevance in order to highlight who deserves priority and how (Neville et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This attitude enables the maximization and maintenance of a favorable position in relation to all organizational interests in strategic decision making (Friedman et al, 2004). Thus, successful organizational management depends on the correct identification of stakeholders and subsequent assessment of their actual relevance in order to highlight who deserves priority and how (Neville et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Sotiriadou (2009) argues that some stakeholders gain their greatest power in terms of the control they hold over the resources needed by the club. This salience reflects the priority attributed by managers to ensuring good organizational management involving leveraging the operating input of stakeholders in order to improve this performance (Samaras, 2010;Neville et al, 2011). …”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…The degree to which the actions and inactions of a stakeholder are accepted by society. Mitchell et al, 1997;Neville et al, 2011;Jonker and Foster, 2002;Mitchell et al, 1997 Stakeholder Urgency…”
Section: Attributes Definitionmentioning
confidence: 99%
“…More recent studies have refined stakeholder salience theory by means of theoretical contributions, stressing the importance of 'stakeholder proximity' (Driscoll and Starik 2004), interactions between stakeholders (Neville and Menguc 2006) and stakeholder attributes (Neville et al 2011), family firm contexts (Mitchell et al 2011), corporate culture (Jones et al 2007), and other stakeholders' perceptions of salience (Tashman and Raelin 2013). More recent empirical research has suggested more stakeholder characteristics, such as trust and learning potential (Myllykangas et al 2010).…”
Section: Prior Literature and Hypotheses Developmentmentioning
confidence: 99%
“…The websites of these NGOs were also consulted to find out whether these are internationally organised and if they engage in coalitions with other NGOs. The rationale for including this information is that NGOs with local branches in different countries will have greater availability of resources than those operating from one country, and coalitions of NGOs will be more powerful than each of the NGOs individually (Eesley and Lenox 2006;Neville et al 2011). Pooling this Footnote 6 continued information resulted in 12 categories of NGOs, ranging from small local NGOs that are not engaged in coalitions (power level = 1) to large international NGOs that are part of a coalition (power level = 12).…”
Section: Measures For Explanatory Variablesmentioning
confidence: 99%